Presence and antibiotic susceptibility of Listeria monocytogenes in retail meat and meat products - DoÄŸruer, Yusuf; Telli, Nihat; Telli, Arife Ezgi; GÃ¼ner, Ahmet (International Journal of Biological Research, 2015)
In this study total of 200 samples including red meat, ready to eat meat (RTE) and traditional red meat products were taken from butcher shops and supermarkets and analyzed for the presence of L. monocytogenes. Presence of Listeria spp. was investigated with cultural and PCR methods. Susceptibility of the isolates to 18 antibiotics were determined by disk diffusion method.19 out of 200 samples (9.5 %) were found to be contaminated with Listeria spp. The isolates were identified as L.monocytogenes, L. innocua, L. seeligeri, L. welshimeri, L. ivanovii; 22.10 %, 55.79 %, 11.58 %, 6.32 %, 4.21 % respectively. L. monocytogenes were isolated from meat pieces (2/40), minced meat (3/40) and hamburger (1/20).All of the L. monocytogenes isolates were susceptible to three antibiotics (Amoxycillin/Clavulonic acid, Sulphamethoxazole/ Trimethoprim and Vancomycin) and resistance to one antibiotic (Clindamicin).As a result, it was evaluated that minced meat and meat pieces was the highest rate (83.3 %, 5/6) of contamination with L. monocytogenes. Determination of non-pathogenic Listeria spp. is found to be important because of the indicator of L. monocytogenes. Hereby, the results presented in this study indicated the potential risk of raw meat and meat products on infection with L. monocytogenes.